PENGARUH PENGGUNAAN MURAL UNTUK MEMBANGUN KARAKTER ANTI-BULLYING DI PAUD KUNCUP MEKAR - Renita, Lusia; Arif, Muchamad; Mashita, Maya; Suliswati, Yeksi Dwi (Universitas Narotama, 2024)
This study aims to identify the benefits of murals in building anti-bullying characters in early childhood at PAUD Kuncup Mekar. Bullying in early childhood often appears in the form of verbal or physical behavior that can have an impact on children's social and emotional development. Through attractive visual media such as murals, moral messages can be conveyed creatively and effectively. This study uses a descriptive qualitative research method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that murals can be an effective educational media in conveying anti-bullying values, building empathy, and creating a positive learning environment. The responses of teachers, children, and parents to the existence of murals are also positive, because they help children understand and internalize anti-bullying attitudes in a fun way. Keywords: Mural, Anti-Bullying Character, Early Childhood Education